The Influence of Teacher Attitude, Self-Efficacy, and Teaching Creativity on Student Motivation in Economics Social Studies at SMP Negeri 9 Marusu - Hasnawi Hasnawi; Elpisah Elpisah; Syarifuddin Syarifuddin; Saripuddin Saripuddin; Suarlin Suarlin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to: (1) determine the influence of teacher Self Efficacy on students’ learning motivation in Economics Social Studies; (2) determine the influence of teachers’ teaching creativity on students’ learning motivation; (3) determine the influence of teacher attitudes on students’ learning motivation; (4) analyze the simultaneous influence of teacher Self Efficacy, teaching creativity, and teacher attitudes on students’ learning motivation; and (5) identify the most dominant variable affecting students’ learning motivation at SMP Negeri 9 Marusu, Maros Regency. The research was conducted from September to November 2025 using an associative quantitative approach with an ex-post facto design. The sample consisted of 155 students selected through proportional random sampling. The research instrument was a Likert-scale questionnaire that had passed validity and reliability testing. Data were analyzed using classical assumption tests and multiple linear regression with the help of SPSS. The results of the study indicate that: (1) teacher Self Efficacy has a significant partial effect on students’ learning motivation (t = 3.606, Sig. = 0.000), but becomes insignificant in the simultaneous model (t = –0.531, Sig. = 0.596); (2) teaching creativity has a positive and significant partial effect (t = 5.852, Sig. = 0.000); (3) teacher attitudes have a positive and significant effect (t = 8.008, Sig. = 0.000) and are the most dominant variable, as shown by the highest regression coefficient (B = 1.456; Beta = 0.916); (4) simultaneously, teacher Self Efficacy, teaching creativity, and teacher attitudes significantly influence students’ learning motivation (F = 38.854, Sig. = 0.000); and (5) teacher attitudes are the most dominant predictor, as indicated by B = 1.456 and Beta = 0.916. This means that the more positive the teacher's attitude, the higher the students' learning motivation.